2017
DOI: 10.1590/1413-812320172211.22092017
|View full text |Cite
|
Sign up to set email alerts
|

Proteção social e política pública para populações vulneráveis: uma avaliação do Benefício de Prestação Continuada da Assistência Social - BPC no Brasil

Abstract: This paper describes the historical development and profile of Continuous Cash Benefit (BPC) applicants, intended for poor elderly and people with disabilities, which, since 2009, uses eligibility criteria based on the International Classification of Functioning, Disability and Health (ICF) of the WHO and is aligned with the UN Convention on the Rights of Persons with Disabilities. The behavior of benefits was determined from the analysis the coefficients of the general and non-judicial grants between 1998 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…Once we found that rejections were higher than concessions, a fact also veri ed by Duarte et al 26 , the non-ful llment of the disability criteria for access to BPC, pointed out as the main cause of rejection, contradicts studies carried out in which the biggest problem for rejection to requests the per capita monthly income with above ¼ of a minimum wage 3,27 . However, after the implementation of the social assessment, the main reasons for rejections were disability considered temporary and absence of incapacity for independent life and work (64.09%) 15 , which may indicate the lack of knowledge in considering the impairment as a disability for the reason of the rejections³.…”
Section: Discussionsupporting
confidence: 37%
See 2 more Smart Citations
“…Once we found that rejections were higher than concessions, a fact also veri ed by Duarte et al 26 , the non-ful llment of the disability criteria for access to BPC, pointed out as the main cause of rejection, contradicts studies carried out in which the biggest problem for rejection to requests the per capita monthly income with above ¼ of a minimum wage 3,27 . However, after the implementation of the social assessment, the main reasons for rejections were disability considered temporary and absence of incapacity for independent life and work (64.09%) 15 , which may indicate the lack of knowledge in considering the impairment as a disability for the reason of the rejections³.…”
Section: Discussionsupporting
confidence: 37%
“…As for the age group, the prevalence of both requirements and concessions was of adults as expected due to the target population of this study. However, the fact that the bene t grant to adolescents overcame the rejections is coupled with the fact that up to the age group 15-19 years old, the concessions overcame the rejections, contrary to what occurs at higher age intervals 26 . The presence of 29 elderly people over 65 years old among the bene ciaries draws our attention.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The presence of the preschool age group (2-7 years old) is possibly related to the onset of clinical manifestations of autism, the main diagnosis found among the applicants. According to the American Psychiatric Association (APA), the onset of signs and symptoms of autism, and consequently its diagnosis, usually begin around 3 years old (American Psychiatric Association, 2019; Duarte et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pessoas com deficiência e idosos têm direito a receber, desde 1996, o Benefício de Prestação Continuada (BPC), uma transferência incondicional de renda no valor de um salário-mínimo mensal, configurando-se como o maior programa de transferência direta de renda, em termos de volume de recursos no país (BRASIL, 1998;BRASIL, 1995;BRASIL, 2007). É um dos mais importantes mecanismos de proteção social às pessoas que se encontram em situação de dupla vulnerabilidade dada a condição de extrema pobreza e idade avançada e/ou presença de deficiência mental ou física (DUARTE et al, 2017;JACOUD;MESQUITA;PAIVA, 2017). Trata-se de um benefício assistencial e não previdenciário, portanto, não contributivo.…”
Section: Introduçâounclassified